THE ROLE OF US-BASED FDI FLOWS FOR GLOBAL OUTPUT DYNAMICS. (27th July 2017) - Huber, Florian; Fischer, Manfred M.; Piribauer, Philipp
Abstract : This paper uses a global vector autoregressive (GVAR) model to analyze the relationship between foreign direct investment (FDI) inflows and output dynamics in a multicountry context. The GVAR model enables us to make two important contributions: First, to model international linkages among a large number of countries, which is a key asset given the diversity of countries involved, and second, to model foreign direct investment and output dynamics jointly. The country-specific small-dimensional vector autoregressive submodels are estimated utilizing a Bayesian version of the model coupled with stochastic search variable selection priors to account for model uncertainty. Using a sample of 15 emerging and advanced economies over the period 1998:Q1–2012:Q4, we find that US outbound FDI exerts a positive long-term effect on output. Asian and Latin American economies tend to react faster and also stronger than Western European countries. Forecast error variance decompositions indicate that FDI plays a prominent role in explaining gross domestic product fluctuations, especially in emerging market economies.